Explain the professional identity of nursing during COVID‐19 pandemic - Tooba Hoseini Azizi; Saideh Varasteh; Maryam Esmaeili (Wiley, 2024)
Abstract Aim To explore the professional identity of nursing during the COVID‐19 pandemic in Iran. Professional identity guides nurses' interaction with patients. In the COVID‐19 pandemic, recent developments in society's view of the nursing profession are expected to change the perception of nurses' professional identities. Design The qualitative study used a conventional content analysis approach. Methods Data were collected using in‐depth semi‐structured interviews from June 2020 to January 2021. Data analysis was performed using Landman and Granheim's analysis and Lincoln and Guba's criteria to ensure the data's rigour. Results After analysing the 20 interviews with 17 participants, including 11 nurses with an average age of 32.63 ± 6.71 years and six varius community members with an average age of 38.66 ± 5.85 years, three main categories were formed: (1) The dual role of the media in the two subcategories (the positive role and the negative role of the media), (2) Changes in public view of nursing during the COVID‐19 pandemic (respect for avoidance and understanding the value of nursing practice) and (3) Change of professional identity by showing self‐sacrifice (dealing with adversity and commitment to professional obligations). Conclusion The image in the public view of the nursing profession during the COVID‐19 pandemic media differs from before and shows self‐sacrifice, professional commitment and humanity in nursing. Nurses' experience of caring during the COVID‐19 pandemic has positively affected their professional identity; however, they are concerned about the instability of improving the nursing image in society. Impact Nursing leaders and policymakers can utilize media platforms to portray the nursing profession in a positive light and emphasize the scientific capabilities of nurses. This approach goes beyond highlighting sacrifice and compassion, aiming to shift societal perceptions of nursing and bolster the professional identity of nurses. Reporting Method We used the COREQ (COnsolidated criteria for REporting Qualitative research) checklist as a reporting method. Patient or Public Contribution No patient or public contribution.